Antimony-ligated dysprosium single-molecule magnets as catalysts for stibine dehydrocoupling. Issue 3 (2nd December 2016) - Pugh, Thomas; Chilton, Nicholas F.; Layfield, Richard A.
Abstract : The synthesis of antimony-ligated dysprosium SMMs is described in addition to the unexpected reactivity of the SMMs in stibine dehydrocoupling catalysis. Abstract : Single-molecule magnets (SMMs) are coordination compounds that exhibit magnetic bistability below a characteristic blocking temperature. Research in this field continues to evolve from its fundamental foundations towards applications of SMMs in information storage and spintronic devices. Synthetic chemistry plays a crucial role in targeting the properties that could ultimately produce SMMs with technological potential. The ligands in SMMs are invariably based on non-metals; we now report a series of dysprosium SMMs (in addition to their magnetically dilute analogues embedded in yttrium matrices) that contain ligands with the metalloid element antimony as the donor atom, i.e. [(η 5 -Cp′2 Dy){μ-Sb(H)Mes}]3 (1-Dy ) and [(η 5 -Cp′2 Dy)3 {μ-(SbMes)3 Sb}] (2-Dy ), which contain the stibinide ligand [Mes(H)Sb] − and the unusual Zintl-like ligand [Sb4 Mes3 ] 3−, respectively (Cp′ = methylcyclopentadienyl; Mes = mesityl). The zero-field anisotropy barriers in1-Dy and2-Dy are U eff = 345 cm −1 and 270 cm −1, respectively. Stabilization of the antimony-ligated SMMs is contingent upon careful control of reaction time and temperature. With longer reaction times and higher temperatures, the stibine pro-ligands are catalytically dehydrocoupled by the rare-earth precursor complexes. NMR spectroscopic studies of the yttrium-catalysed dehydrocoupling reactions reveal that1-Y and2-Y are formed during the catalytic cycle. By implication, 1-Dy and2-Dy should also be catalytic intermediates, hence the nature of these complexes as SMMs in the solid-state and as catalysts in solution introduces a strategy whereby new molecular magnets can be identified by intercepting species formed during catalytic reactions.